The Impact of Blockchain on Business and Economics: Analysis of Theory and Implementation - Chandra Lukita; Silva Wulandari; Syahrul Muarif Wahid; Tri Widiyatmoko (IAIC Bangun Bangsa, 2024)
Blockchain technology has become a powerful disruptive force that has significant effects on economics and business. This article provides a comprehensive examination of the theoretical underpinnings and real-world applications of blockchain in the business and economic domains. The paper explores the foundational ideas of blockchain technology and examines how it affects data security, operational effectiveness, and transaction transparency. In addition, it looks into practical blockchain applications in a variety of industries and analyzes the potential and problems that come with their acceptance. This analysis intends to offer important insights into the revolutionary potential of blockchain technology and its consequences for business practices and economic systems through a thorough review of the body of existing literature and case studies.